Five Visions of Yang Zhu Before He Became a Philosopher - Carine M. G. Defoort (Asian Studies, 2020)
This paper traces the consecutive emergence of five important portrayals of Yang Zhu before he became a philosopher in the Republic. In the late Zhou, he was portrayed as a rival in debate and a defender of physical or personal integrity. From the Han onward, he became part of a rhetorical trope based on Mencius’ portrayal. In the Wei Jin he was a prominent figure in his own right. The fourth portrayal, from the Song onward, contained reflections on his thought in the shadow of Mozi and Confucian orthodoxy. Finally, in the late Qing, Kang Youwei presented him as a minor political reformer responding to Confucius’ reform plans. These layers contributed in various ways to the nowadays almost exclusive presentation of Yang Zhu as a philosopher, a defender of social tolerance, autonomy, or individual freedom. The rich variety of the portrayals has too often been sacrificed for this relatively homogeneous portrayal.